On the Frontiers of History Rethinking East Asian Borders - Morris-Suzuki, Tessa (ANU Press, 2020)
Why is it that we so readily accept the boundary lines drawn around nations or around regions like 'Asia' as though they were natural and self-evident, when in fact they are so mutable and often so very arbitrary? What happens to people not only when the borders they seek to cross become heavily guarded, but also when new borders are drawn straight through the middle of their lives? The essays in this book address these questions by starting from small places on the borderlands of East Asia and looking outwards from the small towards the large, asking what these 'minor pasts' tell us about the grand narratives of history. In the process, it takes the reader on a journey from Renaissance European visions of 'Tartary', through nineteenth-century racial theorising, imperial cartography and indigenous experiences of modernity, to contemporary debates about Big History in an age of environmental crisis.